Normative Protection of Traditional Knowledge and Traditional Cultural Expressions in Indonesia - Theofany, Gabriel (Faculty of Law, Mulawarman University, 2018)
It is undeniable that the flow of globalization plays a major role in every aspect of state life, including the field of law and the legal product itself. Indonesia as a WTO member is obliged to ratify various types of international agreements to be made into domestic law products in the form of the Law. One of the important issues that must be protected is Intellectual Property Rights which is compiled based on the TRIPs standard. In its development, the concepts and characteristics of IPR have caused losses to developing countries such as Indonesia which have many assets in the form of traditional knowledge and traditional cultural expressions held by local communities. The IPR legal regime cannot accommodate the protection of traditional knowledge and traditional cultural expressions as a whole. The direction of legal regulation that protects traditional knowledge and traditional cultural expressions today is to form a new legal product that is specifically outside the IPR regime. The Bill on Traditional Knowledge and Traditional Cultural Expressions has long been composed by Indonesia since 2008 and included in the 2009-2014 National Legislation Program. But even until now there has been no approval made by the government. The normatification of this bill is very important to be done so that it can be given that traditional knowledge and traditional cultural expressions can be used as an aid for advancing the nation's economy. By using normative legal research methods and qualitative approaches, this study concludes that the IPR legal regime in Indonesia has not been able to provide maximum protection to traditional knowledge and traditional cultural expressions. Therefore, it is very important to discuss and ratify the Bill on Traditional Knowledge and Traditional Cultural Expressions to become products law to guarantee protection and provide economic benefits to the State and society.